A chaotic based integrity verification and encryption model for real-time VANET - Kareemulla Shaik; Dr. Md. Ali Hussain (Institute of Advanced Engineering and Science, 2019)
Integrity and data privacy are the main security parameters between the vehicle and roadside unit (RSU) over large VANETs. The integrity of the vehicle is used to check its identity against the neighboring nodes, whereas data privacy ensures that the data of a vehicle has not been altered during the communication process. VANETs provide vehicles to give information about the security parameters and identity to vehicle to infrastructure communication and vehicle to vehicle communication. Most of the traditional VANETs are vulnerable to data security, integrity and authentication due to change in dynamic topology. Also, Traditional security models require limited data size for data security between the V2V or V2I. In this paper, an integrity verification model and non-linear double encryption model were proposed and implemented on large geographical VANET map. The main objective of the proposed model is to improve the security of the V2V communication in large VANETs. Experimental results proved that the proposed security model has less computation cost for encryption model and higher bit change during integrity verification compared to the existing approaches.